Perancangan Sistem Monitoring dan Evaluasi Bantuan Usaha Pertanian pada Kementerian Pertanian Ri - Kurniawan, Yohannes; Luhukay, Devyano; Titan, Titan (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The main problems of current system in agriculture ministry is sub-optimal information retrieval of realization and development of agriculture capital and production facilities subvention. Therefore, this research aims to analyze and design information system for monitoring and evaluation of subvention of agriculture capital and production facilities. This information system is developed based on internet technology to help the main team (agriculture minister and technical team of directorate agriculture department), coach team of provincial agriculture office, and technical team of district/city agriculture office to access the accurate information related realization and development of agriculture business any where and any time. It is designed with OOAD (object oriented analysis and design) method by using UML notation (use case diagram, class diagram, component architecture and user interface design). This research produces a design of information system for subvention monitoring and evaluation of agriculture capital and production facilities for the ministry of agriculture RI.